Transforming research and pedagogy in higher education through scientific inquiry steps - Mpuangnan, Kofi Nkonkonya; Gugulethu, Buthelezi Penelope Zamashenge (Edelweiss Applied Science and Technology, 2024)
This research aims to investigate how to transform study and pedagogy in higher education through scientific inquiry steps. Scientific research serves as the foundation for human development. It drives humanity forward into discovery and innovation. The purpose of this study is to explore how teachers and researchers apply scientific inquiry steps to improve research and pedagogy in higher education in South Africa. Constructivist theory serves as the foundation for the study. Therefore, we employed a qualitative method and phenomenology design to explore the lived experiences of participants. The participants included ten experienced researchers doubling as teachers in the field of science education. We selected these participants from ten public universities in South Africa using a purposive sampling technique. The main instrument for data collection was a semi-structured interview schedule, which covered scientific inquiry steps. Recordings were made of the data with the permission of the participants, later transcribed into a notebook, and analyzed thematically. The findings indicated that teachers and researchers were aware of the scientific inquiry steps. Most of them benefited from scientific inquiry, which included constantly refining methods, embracing diverse perspectives, and revisiting hypotheses and experiments. Also, scientific inquiry steps enhanced the effectiveness of their teaching practices and provided them with a reliable scope for making informed decisions in the ever-evolving educational environment. This study has practical implications, including creating opportunities in higher education for both prospective teachers and emerging researchers to acquire a rigorous education in the scientific inquiry steps. This approach forms the bedrock for acquiring knowledge and promoting best practices in education.